Penanganan Korban Kekerasan Seksual Di Lingkungan Perguruan Tinggi - Zarkasi, A; Siregar, Elizabeth (PAMPAS: Journal of Criminal Law, 2024)
This study is aimed at understanding forms of sexual violence in higher education, both verbal, non-verbal, physical and non-physical, both direct and indirect, which are not yet understood by the academic community. Apart from that, to analyze how victims of sexual violence are handled in higher education environments based on Minister of Education and Culture Regulation Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments. Based on the provisions of the Minister of Education and Culture, there are 21 types or forms of sexual violence regulated in this regulation, some of the acts in the Minister of Education and Culture and Technology have never previously been regulated in criminal law regulations. Handling sexual violence in the tertiary environment is carried out by providing assistance, protection, imposing administrative sanctions and recovering victims. Administrative sanctions will be imposed if the perpetrator is proven guilty. In the event that the perpetrator has carried out sanctions, whether mild or moderate, the obligation that the perpetrator must carry out is to carry out counseling, in accordance with Article 14 Number 5 and Number 7. However, this article is not clear regarding the criteria for a credible institution to carry out counseling and there are no assessment indicators that contain that the perpetrator has no potential to repeat the act and can carry out activities again on campus. Because this is important, because only on the basis of this counseling report can the university leadership issue a certificate stating that the perpetrator has carried out sanctions and can carry out activities on campus. Suggestions from the discussion, regarding the forms of sexual violence regulated in the Minister of Education and Culture Regulation, require explanations and concrete forms of abstract types of sexual violence. Furthermore, it is necessary to include in the Permendikbudristek guidelines regarding the criteria for counseling institutions for perpetrators, as well as indicators to be able to state that the perpetrator has no potential to repeat the act. ABSTRAK Kajian ini ditujukan untuk memahami bentuk kekerasan seksual di perguruan tinggi, baik yang bersifat verbal, non verbal, fisik dan non fisik, baik secara langsung maupun tidak langsung yang belum dipahami civitas akademika. Selain itu, untuk menganalisis bagaimana penanganan korban kekerasan seksual di lingkungan perguruan tinggi berdasarkan Permendikbudristek Nomor 30 Tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi. Berdasarkan ketentuan Permendikbudristek ada 21 jenis atau bentuk kekerasan seksual yang diatur dalam peraturan tersebut, yang beberapa perbuatan dalam Permendikbudristek tersebut tidak pernah diatur sebelumnya dalam aturan hukum pidana. Penanganan kekerasan seksual di lingkungan perguruan tinggi dilakukan dengan memberikan pendampingan, pelindungan, pengenaan sanksi administrasi dan pemulihan korban. Pengenaan sanksi administrasi dilakukan jika pelaku terbukti bersalah. Dalam hal pelaku telah melaksanakan sanksi baik ringan maupun sedang, kewajiban yang harus dilakukan pelaku menjalankan konseling, sesuai Pasal 14 Angka 5 dan Angka 7. Namun pasal ini, belum jelas, terkait kriteria lembaga yang kredibel untuk melaksanakan konseling dan tidak ada indikator penilaian yang memuat bahwa pelaku tidak berpotensi mengulang perbuatan dan dapat melaksanakan aktivitas kembali di kampus. Sebab hal ini menjadi penting, karena hanya atas dasar laporan konseling inilah pimpinan perguruan tinggi dapat mengeluarkan surat keterangan yang menyatakan bahwa pelaku telah melaksanakan sanksi dan dapat berkegiatan di kampus. Saran dari pembahasan, terkait bentuk kekerasan seksual yang diatur dalam Permendikbudristek perlu penjelasan dan bentuk konkrit jenis kekerasan seksual yang bersifat abstrak. Selanjutnya perlu dimuatkan dalam pedoman Permendikbudristek terkait kriteria lembaga konseling pelaku, serta inidkator untuk dapat dinyatakan bahwa pelaku tidak berpotensi mengulangi perbuatan.